Programma: 18 juli The Fabulous Thunderbirds; 19 juli Mutabaruka; 27 juli Love/Hate; 28 juli Greater Than One
Programma: 18 juli The Fabulous Thunderbirds; 19 juli Mutabaruka; 27 juli Love/Hate; 28 juli Greater Than One.